Psychoanalysis Goes online: psychoanalytic resources on the internet - Laszig, Parfen (Social science computer review, 2000)
There is no question that the Internet as a zeitgeist phenomenon poses for psychoanalysts the question of individual access, be it in form of theoretic analysis or by direct use of this tool. In this illustrative search, the author describes specific resources systematically and offers some guidance for navigation for personal use of this medium. Following Goethe's dictum that a thing has to be found first of all if you would like to know where it is located, the author used web search engines and electronic access to libraries and databases to find associations, societies, institutes, discussion groups, electronic journals, and other resources. The article ends with a discussion of the capabilities and limitations of network supported searches.
Gesehen am 11.03.2021